2011
DOI: 10.2147/vhrm.s22435
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the responses to shear stress in human umbilical vein endothelial cells

Abstract: Background:African American ethnicity is an independent risk factor for exaggerated oxidative stress, which is related to inflammation, hypertension, and cardiovascular disease. Recently, we reported that in vitro oxidative stress and inflammation levels differ between African American and Caucasian human umbilical vein endothelial cells (HUVECs), African American HUVECs having higher levels of both. However, it remains to be shown whether the cells would respond differently to external stimuli.Methods:We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 19 publications
3
43
1
Order By: Relevance
“…Our data agree with previously reported donor-dependent variability of HUVECs exposed to laminar shear stress [59], and might have implications for the use of near-infrared-emitting quantum dots in clinical vascular imaging applications.…”
Section: Nontargeted Pegylated Near-infrared Emitting Qtracker ® 800 supporting
confidence: 92%
“…Our data agree with previously reported donor-dependent variability of HUVECs exposed to laminar shear stress [59], and might have implications for the use of near-infrared-emitting quantum dots in clinical vascular imaging applications.…”
Section: Nontargeted Pegylated Near-infrared Emitting Qtracker ® 800 supporting
confidence: 92%
“…NO levels were indirectly measured by determining NO end-products, nitrate and nitrite, using an Enzo Life Sciences/ Assay Designs assay kit as described previously (18). Absorbance was read at 540 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the essential hypertension in African Americans has been explained by endothelial cell dysfunction (Kalinowski et al 2004), and it has been hypothesized that an insufficiency of NOS activity is associated with a gene variant that reduces the normal production of NO (Martinez Cantarin et al 2010). A study supporting this hypothesis found that umbilical arteries from African Americans exhibited greater oxidative stress and inflammation during exposures to increased shear forces than did those from Caucasian Americans (Feairheller et al 2011 a , 2011 b ). One approach to overcoming NO deficiency is dietary supplementation of nitrate and increasing the bioavailability of NO by using foods such as beetroot juice (Miller et al 2012).…”
Section: Introductionmentioning
confidence: 94%